# Elements of Algebra: For Colleges, Schools, and Private Students, Βιβλίο 2

Wilson, Hinkle & Company, 1866 - 406 σελίδες

### Τι λένε οι χρήστες -Σύνταξη κριτικής

Δεν εντοπίσαμε κριτικές στις συνήθεις τοποθεσίες.

### Δημοφιλή αποσπάσματα

Σελίδα 136 - Multiply the divisor, thus increased, by the last figure of the root; subtract the product from the dividend, and to the remainder bring down the next period for a new dividend.
Σελίδα 289 - Take the first term from the second, the second from the third, the third from the fourth, &c. and the remainders will form a new series, called the first order of
Σελίδα 35 - Obtain the exponent of each literal factor in the quotient by subtracting the exponent of each letter in the divisor from the exponent of the same letter in the dividend; Determine the sign of the result by the rule that like signs give plus, and unlike signs give minus.
Σελίδα 39 - Divide the first term of the dividend by the first term of the divisor, and write the result as the first term of the quotient. Multiply the whole divisor by the first term of the quotient, and subtract the product from the dividend.
Σελίδα 148 - ... by the last figure of the root, and subtract the product from the dividend ; to the remainder bring down the next period for a new dividend.
Σελίδα 187 - CD, and, on meeting, it appeared that A had traveled 18 miles more than B ; and that A could have gone B's journey in 15 £ days, but B would have been 28 days in performing A's journey.
Σελίδα 68 - Reduce the fractions to a common denominator ; then subtract the numerator of the subtrahend from the numerator of the minuend, and write the result over the common denominator. EXAMPLES. H ,_, Zx . ^ 3x 1. From -^- subtract — . oo . Eeducing to a common denominator, the fractions become Wx 9x "15...
Σελίδα 37 - Since, in multiplying a polynomial by a monomial, we multiply each term of the multiplicand by the multiplier ; therefore, we have the following RULE, FOR DIVIDING A POLYNOMIAL BY A MONOMIAL. Divide each term of the dividend, by the divisor, according to the rule for the division of monomials.
Σελίδα 236 - In any proportion the product of the means is equal to the product of the extremes.
Σελίδα 43 - The square of the difference of two quantities is equal to the square of the first minus twice the product of the first by the second, plus the square of the second.